Find two numbers with a sum of -66 and a difference of -116.

x = one number

y = other number

x + y = -66 {sum is -66}

x - y = -116 {difference is -116}

------------

2x = -182 {added the two equations together}

x = -91 {divided both sides by 2}

x + y = -66 {top equation}

-91 + y = -66 {substituted -91, in for x, into top equation}

y = 25 {added 91 to both sides}

Two numbers are -91 and 25

*To check*

-91 + 25 = -66 {sum is -66}

-91 - 25 = -116 {difference is -116}

© Algebra House

y = other number

x + y = -66 {sum is -66}

x - y = -116 {difference is -116}

------------

2x = -182 {added the two equations together}

x = -91 {divided both sides by 2}

x + y = -66 {top equation}

-91 + y = -66 {substituted -91, in for x, into top equation}

y = 25 {added 91 to both sides}

Two numbers are -91 and 25

*To check*

-91 + 25 = -66 {sum is -66}

-91 - 25 = -116 {difference is -116}

© Algebra House